Candidal Leukoplakia on Patient with Removable Denture - Shiril Paskalis; Anandina Irmagita (Faculty of Dentistry, Universitas Indonesia, 2013)
Candida infection is a common problem in patients using removable dentures, with the most frequent type is denture stomatitis. But other type of candidal infection could also happen in these patients, such as candidal leukoplakia. We reported a 61 years old female patient who complained a painful lesion under her lower removable denture. Oral examination revealed white plaque that could not be rubbed over an ulcer on the lingual part of alveolar processes under the lower removable denture plate, and also an erythematous area on palatum durum above the upper full denture. The patient was suspected to have candidal leukoplakia on the lingual part of the mandible and denture stomatitis on the palate area. The treatment consisted of nystatin oral suspension, chlorhexidine solution, multivitamins, along with denture replacement and oral health education. The entire lesion resolved within 2 months therapy. Candidal infection treatment on denture patient needs not only medication or denture replacement, but also patient compliance to achieve maximal result.